SOSIALISASI PEMBUATAN POSTER MENGGUNAKAN APLIKASI CANVA UNTUK MENINGKATKAN KREATIVITAS SISWA SMPN 1 PATIKRAJA - Ramadhan Saputra; Muqorobin Marufi; Sandya Rifai Putra; Dilaeka Zerosi; Ito Setiawan (JOURNAL SAINS STUDENT RESEARCH, 2026)
Digital literacy skills, specifically in creating visual media, have become essential competencies for junior high school (SMP) students to support both academic activities and independent creativity. However, students at SMP Negeri 1 Patikraja still face difficulties in creating aesthetic and informative designs for school assignments or digital bulletin boards. This socialization activity aims to enhance students' soft skills and creativity through training in the use of the Canva application as a practical and engaging design tool. The method used was participatory training, which included a presentation on basic graphic design, a demonstration of Canva's features, and a hands-on session for creating creative posters. The results showed a 70% increase in participants' understanding and skills in utilizing design features such as template selection, the use of legible typography, and uploading visual elements. Through this activity, students are now able to independently produce professional visual materials to support various school activities.